Studying the extraction of macro and micronutrient elements in dried Stevia plant leaves and stems using pressurised hot water extraction - Zwane, Zinhle (My University, 2023)
Stevia rebaudiana is economically significant because it is utilised as a natural sweetener. This study extracted the macronutrients and micronutrient elements from Stevia rebaudiana using the pressurised hot water extraction (PHWE) technique. The PHWE system consisted of deionised water heated at 81-100ºC and transported through the extraction cell inside an oven. The cell was filled with mixed amounts of dried Stevia rebaudiana powder (1.5 g) and diatomaceous earth. As part of the optimisation, the extraction was done at 50, 100, and 150 ºC at a constant flow rate of 1 mL/min. Microwave digestion was used to compare the quantity of extracted metals to total metal analysis, followed by ICP-OES analysis, in contrast to macronutrients. Calculating the extraction half-lives revealed that the extraction followed first- order reaction kinetics. This may be due to the metals being strongly linked to the ligand. The order of amounts extracted of the micronutrient elements was Fe > Zn > Al> Ni > Co > Cr with Fe being highest in amount extracted and Cr least. The extraction temperature influenced the order of extraction mentioned above. An increase influenced macronutrient elements in extraction time, and the extraction order was K > Ca > Mg. When the metals removed under optimal conditions were compared to the total metals in Stevia rebaudiana biomass for both leaves and stems, it was discovered that PHWE could extract more macronutrient elements than micronutrient elements. The average recovery for macronutrient elements was 1249 mg/kg ± 3, and the average recovery for micronutrient elements was 11.802 mg/kg ± 0.3. Micronutrients extracted at 50,100 and 150 ºC resulted in 2-200 mg/kg concentrations and macronutrients 100-15000 mg/kg. This suggests that Stevia rebaudiana extracts for both stem and leaves from PHWE can easily be used for value additions such as dietary supplements in other foodstuffs and beverages.
A dissertation submitted In fulfilment of the requirements of the degree of Master of Science to the Faculty of Science,School of Chemistry University of the Witwatersrand, Johannesburg, 2022